Glossary of terms for public health genomics (Italian Journal of Public Health, 2006)
In this Glossary the secretariat of PHGEN has compiled some of the terms relevant to Public Health Genomics. A more extensive version of this glossary can be found on the PHGEN-website www.phgen.eu.